As práticas punitivas conforme o modelo socioeconômico capitalista no Ocidente: um panorama da Antiguidade à (Pós-)Modernidade - Valenti, Ricardo de Sant' Anna (2018)
This study presents a panoramic analysis of the criminal practices in comparison with the development of the capitalist model that avenged in the western world, with three objectives: to demonstrate that the criminal practices are adjusted to the current socioeconomic model; to evidence that with the advent of the market economy and the capitalist mentality this phenomenon was concealed by liberal and positivist discourse, so as to (and for the purpose of) discursively legitimize material relations of power; and indicate, in an embryonic way, that the confrontation of this phenomenon in the criminal sciences is done by the broad resistance against the criminalizing manifestations.The examination carried out transcends dogmatic and, in philosophical territory, dialogue with other sciences (such as Sociology and History) in order to allow the interpretation of events in the matrix proposed by Critical Criminology. It starts from the analysis of the socioeconomic model of Antiquity and the medieval period and of the criminal exercises in the transition from the private and divine revenge to the public revenge. Then we analyze the economic and social transformation that began with mercantilism at the end of the Middle Ages, that changed criminalizing action, especially in the light of the economic-political usefulness gained by the modalities of penal sanction – a historical circumstance amply demonstrated by the history of imprisonment – a transformation that is consolidated with the Modernity of Illumination and in the positivist discourses that followed it. Finally, we come to the appreciation of the social and economic characteristics that can be punctuated today as identifiers of a post period: the postmodern criminal practices that allow the management of a population layer excluded from the process of globalization (especially economic), in the wake of neoliberal policies, in accordance with the consumer society of today. In this course, the hermeneutic-critical diagnosis of strategies, discourses, symbols and instruments that represent the punitive activity of the so-called modern state is presented